Smartphone addiction and phubbing behavior among university students: a moderated mediation model by fear of missing out, social comparison, and loneliness - Bajwa, Ruqia Safdar; Abdullah, Haslinda; Zaremohzzabieh, Zeinab; Wan Jaafar, Wan Munira; Abu Samah, Asnarulkhadi (Frontiers Media, 2022)
Introduction: This article examines mediators and moderators that may explain the link between smartphone addiction and phubbing behavior using a sample of 794 university students. Methods: A mediation model was tested to test the hypothesis that social comparison orientation and fear of missing out would mediate the link between smartphone addiction and phubbing behavior. Additionally, a moderated mediation model was leveraged to examine loneliness as a moderator within the hypothesized model. The data collected were analyzed using SPSS. Results and discussion: The findings show a significant positive relationship between smartphone addiction and phubbing behavior. The findings confirm the hypothesized associations and reveal that smartphone addiction is positively linked to phubbing behavior. The link, on the other hand, is partially and sequentially mediated by the fear of missing out and social comparison orientation. As a result, both mediators might be regarded as proximal variables of phubbing behavior. Moreover, the associations between both smart addiction and phubbing behaviors as well as social comparison orientation and phubbing behaviors are moderated by loneliness. These two effects were stronger for university students with high loneliness than for those with low loneliness. This study addresses a major gap in the clinical psychology literature through the attempt to explore the relationship between smartphone addiction and increased phubbing behavior among university students.